HTK-N: Modified Histidine-Tryptophan-Ketoglutarate Solution—A Promising New Tool in Solid Organ Preservation - Mohr, Annika (Int J Mol Sci, 2020)
To ameliorate ischemia-induced graft injury, optimal organ preservation remains a critical hallmark event in solid organ transplantation. Although numerous preservation solutions are in use, they still have functional limitations. Here, we present a concise review of a modified Histidine-Tryptophan-Ketoglutarate (HTK) solution, named HTK-N. Its composition differs from standard HTK solution, carrying larger antioxidative capacity and providing inherent toxicity as well as improved tolerance to cold aiming to attenuate cold storage injury in organ transplantation. The amino acids glycine, alanine and arginine were supplemented, N-acetyl-histidine partially replaced histidine, and aspartate and lactobionate substituted chloride. Several in vitro studies confirmed the superiority of HTK-N in comparison to HTK, being tested in vivo in animal models for liver, kidney, pancreas, small bowel, heart and lung transplantation to adjust ingredients for required conditions, as well as to determine its innocuousness, applicability and potential advantages. HTK-N solution has proven to be advantageous especially in the preservation of liver and heart grafts in vivo and in vitro. Thus, ongoing clinical trials and further studies in large animal models and consequently in humans are inevitable to show its ability minimizing ischemia-induced graft injury in the sequel of organ transplantation.